How to solve inverse scattering problems without knowing the source term: a three-step strategy. (4th September 2019) - Graff, Marie; Grote, Marcus J; Nataf, Frédéric; Assous, Franck
Abstract: The solution of inverse scattering problems always presupposed knowledge of the incident wavefield and require repeated computations of the forward problem, for which knowing the source term is crucial. Here we present a three-step strategy to solve inverse scattering problems when the time signature of the source is unknown. The proposed strategy combines three recent techniques: (i) wave splitting to retrieve the incident and the scattered wavefields, (ii) time-reversed absorbing conditions ( TRAC ) for redatuming the data inside the computational domain, (iii) adaptive eigenspace inversion (AEI) to solve the inverse problem. Numerical results illustrate step-by-step the feasibility of the proposed strategy.